Aggregation‐Induced Orange‐to‐Red Fluorescence of 2, 5‐Bis(diarylamino)terephthalic Acid Dithioesters. Issue 36 (15th November 2016) - Shimizu, Masaki; Fukui, Hiroki; Natakani, Masaki; Sakaguchi, Hiroshi
Abstract : π‐conjugated systems substituted by electron donors (D) or acceptors (A) are useful platforms for various kinds of organic optoelectronic materials. The exploration and development of new donors and acceptors can expand the possible molecular designs of D–π–A‐type electronic structures. Herein we report 2, 5‐bis(diarylamino)terephthalic acid dithioesters, in which organosulfanylcarbonyl groups serve as electron acceptors, as new fluorophores exhibiting efficient solid‐state emission. The absorption spectra of the thioesters in toluene show two bands, with the smaller band located at the longer wavelength corresponding to the intramolecular charge‐transfer transition from the diarylamino to organosulfanylcarbonyl groups. The dithioesters are faintly fluorescent in toluene, but exhibit efficient orange‐to‐red emission in the powder form; therefore, aggregation‐induced emission was observed. Compared with the corresponding terephthalic acid diesters, the fluorescence spectra of the dithioesters in the powder form are significantly redshifted. Abstract : Bis(diarylamino)terephthalic acid dithioesters in powder form show efficient fluorescence in the orange‐to‐red region. Because the emission colors of the corresponding bis(diarylamino)terephthalic acid diesters are green‐to‐yellow, the use of organosulfanylcarbonyl groups as electron acceptors is beneficial for attaining redshifted emission compared with the corresponding diesters.